2013
DOI: 10.1001/jamapediatrics.2013.2395
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcomes at 4 to 8 Years of Children Born at 22 to 25 Weeks’ Gestational Age

Abstract: Knowledge of these data, including the limitations, should facilitate discussion during the shared decision-making process about care plans for these infants, particularly in centers without their own data. More prospective, high-quality, complete cohorts are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 64 publications
6
62
1
4
Order By: Relevance
“…Z-scores for healthy subjects have been calculated for the IOS outcome variables AX and R [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] in Finnish and Mexican children. 26,27 Depending on which reference used in the calculations, we found that the mean z-score for AX (before reversibility test) among healthy 6½-year-old children participating in our study (those with asthma reductions of 16% associated with mild BPD and 19% for moderate to severe BPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Z-scores for healthy subjects have been calculated for the IOS outcome variables AX and R [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] in Finnish and Mexican children. 26,27 Depending on which reference used in the calculations, we found that the mean z-score for AX (before reversibility test) among healthy 6½-year-old children participating in our study (those with asthma reductions of 16% associated with mild BPD and 19% for moderate to severe BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Spirometry outcomes in children born extremely preterm did not differ significantly between those born SGA and those born AGA. However, children born SGA had higher R [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] assessed with IOS than those born AGA.…”
Section: Lung Function In Children Born Extremely Preterm and Sgamentioning
confidence: 99%
“…30 Infants born at 22 weeks' gestation have reported rates of moderate to severe neurodevelopmental impairment of 85% to 90%; for infants born at 23 weeks' gestation, these rates are not significantly lower. [29][30][31][32] The risk of permanent, severe neurodevelopmental and other special health care needs affect both the infant and the family and, for some parents, may outweigh the benefit of survival alone. [33][34][35][36] …”
Section: Outcome According To Gestational Agementioning
confidence: 99%
“…Preterm births are associated with neurodevelopmental morbidities, including impairment of cognitive, language and motor function as well as increased risk for autism spectrum disorders [1,2,3,4,5,6,7,8]. Despite improvements in obstetrical and neonatal care in the past few decades, the number of survivors with neurological sequelae that affect quality of life has remained unchanged.…”
Section: Introductionmentioning
confidence: 99%